Plan de mantenimiento preventivo para la maquinaria pesada de la constructora Willerconst. Ltda. del cantón Santo Domingo. año 2014 - Aguirre Naranjo, Edwin Neptalí (2015)
he research proposal was developed in WILLERCONST. Cia. Ltda. Located in Santo Domingo canton suppliers are: the Provincial Council, the City and certain public and private institutions. The population corresponded to operational workers (11) and a head of operations Constructora a technical study was determined for calculating the productivity of heavy equipment also suitable frequency of preventive maintenance of heavy machinery company was determined systematized and monitoring to improve maintenance plan Constructora resources. The results I showed that in machinery, human resources and production processes of the area in question, the main problem that affected Workshops Diesel Heavy, which were the "external repairs" and stoppages damage mechanisms grinders, caused with greater incidence of these machines obsolete. It should take into consideration operations faults absolutely machinery in the maintenance plan, only in the implementation of a systematic maintenance point background use, such as resumes, technical feature of the machine, spare parts in stock, lubrication, operating daily log of the machines, improvements in these points it was lowering the incidence rate in the administrative or corporate efficiency. The alternative solution was by implementing preventive maintenance activities of such equipment and a training program for human resources to operate the assets raised implement, thereby increasing the efficiency of production.